Nature’s Way-Our Way: A Journey Through the Co-Creation and Sharing of an Indigenous Physical Literacy Enriched Early Years Initiative - Froehlich Chow, Amanda; Wahpepah, Kathy; Humbert, M. Louise; Houser, Natalie; Brussoni, Mariana; Erlandson, Marta; Gannon, Amanda; Larmour, Ashley; Stevenson, Erica; Riley, Kathryn; Ali, Fatima (Engaged Scholar Journal, 2025)
Early years are a critical time in the healthy development of young children. It is essential for children to develop healthy bonds with family members to increase well-being. Colonialism has resulted in the loss of many Indigenous activities, intergenerational teachings and relationship-building strategies that encourage wholistic health-promoting behaviours. Research focused on physical activity behaviours among early years children has had limited success. To address these challenges, the Western concept of physical literacy that applies a wholistic approach to physical activity by focusing on physical, social, emotional, and spiritual wellness can align with many Indigenous Ways of Knowing, Being and Doing.Purpose: Our multi-cultural team embarks on a journey to co-create, and expand a physical literacy enriched and culturally rooted initiative designed to promote wholistic wellness.Methodology: Etuaptmumk (Two-eyed Seeing) guides the team through braiding Indigenous Ways of Knowing,Being and Doing in early childhood wellness and land- and nature-based games alongside Western knowledge of developing physical literacy and promoting risky/adventurous play. We apply a pre-mid-post design for the meaningful evaluation of the Nature’s Way-Our Way initiative.Impact: Partnering with communities, we aim to produce 40-45 activity cards to promote physical literacy and wholistic health in Indigenous and non-Indigenous communities.